Novel electrochromic materials based on chalcogenoviologens for smart windows, E-price tag and flexible display with improved reversibility and stability - Song, Ruitong; Li, Guoping; Zhang, Yueyan; Rao, Bin; Xiong, Shanxin; He, Gang (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] A series of electrochromic composites consisting of chalcogenoviologen-based ionic liquids ([C6EVC6][TFSI]2, E = S, Se, Te) and ferrocene-based ionic liquids ([FcC11ImC1][TFSI]) is reported. Electrochromic devices (ECDs) filled with these composites were assembled, demonstrating multiple colors under different voltages, fast switching times, high color contrast ratio, good reversibility and cycle stability. ECDs working as smart windows on a module house could slow down the room temperature rising in hot weather through changing color. In addition, the eye-catching E-price tag and flexible display devices which can show information dynamically, were assembled successfully. This contribution provided a new kind of electrochromic composites-based smart device for intelligent life.